Molekularni mehanizmi nastanka debelosti s poudarkom na vlogi sistema renin-angiotenzin-aldosteron - Černe, Darko (Farmacevtski vestnik, 2016)
In the developed countries obesity is acquiring epidemic proportions, therefore the study of the molecular mechanisms of obesity is an important professional and scientific challenge. The first part of the paper presents the most important physiological basics of utilization of energetic molecules (digestion of nutrients in the gastrointestinal tract, the importance of adipose tissue, cellular metabolism of energetic molecules, fructose metabolism), which are regulated on a systemic level and jointly interrelated by the neurohormonal system. The second part of the paper presents the selected molecular mechanisms of obesity, the role of adipose tissue, the importance of local synthesis of hormones of the renin-angiotensin-aldosterone system and their systemic effects, the role of oxidative stress and the importance of consuming food rich in fructose..
Keywords: Debelost; fruktoza; hormoni; maščobno tkivo; molekularni mehanizmi; multipla skleroza; nevrohormonalni sistem; oksidativni stres